Mass Higher Education in Russia: Features of Dynamics - V. F. Pugach (Высшее образование в России, 2020)
The article considers the massification of higher education in post-Soviet Russia and shows its special aspects against the background of the studentship history in our country from 1917 to 2017. The main cause of the boom in the sphere of higher education at the turn of the century is the social and economic transformation of the society. The emergence of private universities and fee-based education in the public sector of higher education provided opportunities for broad segments of society. The unmet demand for higher education has resulted in an upsurge in the interest to higher education among the society. The similar boom and wave-like dynamics may be traced regarding postgraduate training due to long lasting deficit. The paper presents the results of comparing student body dynamics in universities, postgraduate and doctoral schools and shows the boom synchronicity at the levels of universities and postgraduate schools.